Acceleration of the thermal back-reaction and the finding of a non-photochromic isomer for a negative photochromic binaphthyl-bridged imidazole dimer. Issue 20 (20th February 2023) - Mutoh, Katsuya; Moriyama, Natsuho; Abe, Jiro
Abstract : Our study revealed that incorporating the phenylethynyl group into negative photochromic binaphthyl-bridged imidazole dimers results in a significant acceleration of the thermal back-reaction. Abstract : The development of visible or near-infrared (NIR) light-responsive fast photoswitchable molecules for the real-time, non-contact control of physical and chemical properties has received increased attention because of the non-invasive features to materials and biological tissues. We report a new molecular design to accelerate the thermal back-reaction of the negative photochromic binaphthyl-bridged imidazole dimer, BN-ImD. We also found that irradiation of the BN-ImD derivative with methyl groups on the bridging binaphthyl unit with visible light produced an unprecedented photoreaction product with a unique eight-membered ring structure. These observations provide fascinating clues for the future development of fast negative photochromic molecules.